Theosemiosis: An essay on consilience and the perennial philosophy. - Kalkman, Matthew L. (Sign Systems Studies, 2023)
Can the divide between science and religion be bridged? The current article will present the case for semiotics - and specifically the process of theosemiosis - as that platform of connection. In order to present this argument a key issue that must be tackled is whether there is one underlying function within the category of religion that can be extracted and held accountable in its knowledge claims: what has generally been termed the perennial philosophy. This extracted principle must then be capable of conforming to a broader model of consilience that can contain the knowledge captured in both science and religion. A model that can equally explain the work of Aristotle, Bacon, Galilee, and Einstein as it does Moses, Buddha, Jesus and Krishna, both in an ontological and epistemological sense; and thus a modification and extension of Enlightenment principles in such a way that they can capture the western and eastern notions of that light. In this regard, seeing truly is 'knowing'.